O potrzebie zmian w zakresie kształtowania kompetencji społecznych studentów pedagogiki = The need to change the scope of shaping social competence in students of educational studies - Bąbka, Jarosław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper presents the results of the research on social competence in students of educational studies at the University of Zielona Góra, who major in school counselling and social rehabilitation and prevention. In the study, the author used the social competence questionnaire KK-A(M), the standardized research tool elaborated by Anna Matczak, as well as a questionnaire developed by the author for analysing the social competence e?ects achieved by teachers in classes they conduct.
Keywords: edukacja; kompetencje społeczne; młodzi ludzie w okresie wczesnej dorosłości; education; social competences; young people in the early adulthood